The Influence of Laparoscopic Benign Hysterectomy in Sexual Function - Meritxell Gracia; María Ángeles Martínez-Zamora; Camil Castelo-Branco; Francisco Carmona (IMR Press, 2023)
Objectives: Hysterectomy is the most frequent major surgery performed worldwide in women and in recent years most studies include validated instruments to measure sexual quality of life pre and post operatively. The present review assesses sexual function following abdominal hysterectomy for benign pathology, especially in relation to minimally invasive surgery: laparoscopic and robotics according to different considerations. Mechanism: The uterus has traditionally been considered a sexually functioning organ, so uterine removal has been associated with negative outcomes on patients' sexual function despite limited and controversial evidence. By contrast, reviews conducted in recent years conclude that hysterectomies performed for benign uterine pathology improve patients' sexual function and quality of life. Findings in brief: Some factors associated with surgery have been specially assessed: the combination of hysterectomy with bilateral oophorectomy in patients with benign pathology can lead to alterations in sexual function and should be restricted only to patients at high risk of ovarian cancer, moreover, there is no current scientific evidence to justify performing a subtotal hysterectomy to preserve or improve sexual quality of life over total hysterectomy. Conclusions: postoperative sexual changes have not been demonstrated to mainly depend on surgical approach, in fact, patients who had sexual concerns prior surgery will continue to present them after hysterectomy despite of the vaginal cuff suture approach.